Continuous Professional Development of TVET Teachers: Identifying Trends and Future Research - Wendi, Henson Febri; Komaro, Mumu; Widaningsih, Lilis (Journal of Vocational Education Studies, 2025)
Continuous Professional Development (CPD) for TVET teachers improves the quality of vocational education and ensures relevance to industry advances. This study presents a systematic literature review (SLR) of CPD research trends for TVET teachers over the last ten years (2013-2023), with particular attention to how different CPD models impact classroom effectiveness. Using the PRISMA procedure, article searches were performed in the Scopus database, yielding 48 publications suitable for further study. Despite a large increase in CPD publications, research in developing countries remains scarce, with significant disparities in implementation approaches between developed and developing educational systems. Qualitative approaches dominate methodologically, with apprenticeships, education, and training emerging as primary topics. However, the review reveals limited research on measuring the direct impact of CPD on teacher performance and student outcomes across different educational contexts. These findings point to the need for more integrated, locally based CPD strategies with stronger industry partnerships to enhance the effectiveness and relevance of professional development for TVET teachers. The study provides a foundation for policymakers and researchers seeking to develop context-specific CPD frameworks that balance theoretical knowledge with practical teaching improvements in technical and vocational education.